Natural law and Thomistic juridical realism prospects for a dialogue with contemporary legal theory - Popović, Petar 1983-; Hittinger, F. Russell (Washington, D.C. The Catholic University of America Press, 2022)
Introduction -- The juridical domain of natural law in contemporary legal philosophy -- status quaestionis -- The realistic conception of right and juridicity -- The juridical status of natural law : Villey, Hervada, and Aquinas revisited -- At the intersection between ius and morality : bringing together the Thomistic natural-law tradition -- Walls of separation or prospective points for dialogue? -- Conclusion.
"This book proposes a new approach to the question of the juridical domain of natural law with reference to the classical tools of Thomistic formulation. This book adds something new to the intersection between the normative status of natural law and the essence of the juridical domain"--
Includes bibliographical references and index
Keywords: Natural Law; Law -- Philosophy; Realism; Neo-scholasticism; Ethics; Law ; Philosophy; Natural Law; Neo-scholasticism; Realism